The effects of antimicrobial peptides buCaTHL4B and Im-4 on infectious root canal biofilms - Hu, Ziqiu; Ren, Haixia; Min, Yifan; Li, Yixin; Zhang, Yuyuan; Mao, Min; Leng, Weidong; Xia, Lingyun (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose The primary cause of pulp and periapical diseases is the invasion of bacteria into the root canal, which results from the continuous destruction of dental hard tissues. Effective management of infections during root canal therapy necessitates effectively irrigation. This study aims to investigate the effects of two antimicrobial peptides (AMPs), buCaTHL4B and Im-4, on root canal biofilms in vitro. Methods Two-species biofilms (Enterococcus faecalis and Fusobacterium nucleatum) were selected and anaerobically cultivated. The following treatments were applied: 10 μg/mL buCaTHL4B, 10 μg/mL Im-4, 5 μg/mL buCaTHL4B, 5 μg/mL Im-4, 1 μg/mL buCaTHL4B, 1 μg/mL Im-4, 1% NaOCl, and sterile water. Each group was treated for three minutes. Subsequently, the two strains were co-cultured with 10 μg/mL buCaTHL4B, 10 μg/mL Im-4, 1% NaOCl, and sterile water for 24, 48, and 72 hours. The biofilms were examined using confocal laser scanning microscopy (CLSM) with fluorescent staining, and the percentages of dead bacteria were calculated. Quantitative real-time PCR (qRT-PCR) was employed to assess the variations in bacterial proportions during biofilm formation. Results Compared to 1% NaOCl, 10 μg/mL buCaTHL4B or Im-4 exhibited significantly greater bactericidal effects on the two-species biofilms (p ＜ 0.05), leading to their selection for subsequent experiments. Over a 48-hour period, 10 μg/mL Im-4 demonstrated a stronger antibiofilm effect than buCaTHL4B (p ＜ 0.05). Following a 24-hour biofilm formation period, the proportion of F. nucleatum decreased while the proportion of E. faecalis increased in the sterile water group. In the buCaTHL4B and 1% NaOCl groups, the proportion of F. nucleatum was lower than that of E. faecalis (p ＜ 0.05), whereas in the Im-4 group, the proportion of F. nucleatum was higher than that of E. faecalis (p ＜ 0.05). The proportions of bacteria in the two AMPs groups gradually stabilized after 24 hours of treatment. Conclusion buCaTHL4B and Im-4 exhibited remarkable antibacterial and anti-biofilm capabilities against pathogenic root canal biofilms in vitro, indicating their potential as promising additives to optimize the effectiveness of root canal treatment as alternative irrigants.